Effects of long term diabetogenic high fat diet on bone in ovariectomized female rats. (2nd January 2023) - Dai, Fang; Zhang, Yi; Xu, Dongmei; Liu, Chao; Cao, Qiongqiong; Gui, Li; Lu, Yunxia; Zhang, Qiu
ABSTRACT: A diabetogenic high fat diet (HFD) can be used to induce insulin resistance and obesity in animal models; however, its effects on bone are unknown. We investigated the effects of long term HFD on bone in ovariectomized (OVX) female rats. We used 12-week-old female rats divided randomly into four groups: sham operation (sham), sham operation with HFD (SHFD), OVX and OVX with HFD (OVX + HFD). Ovaries were removed in the OVX and OVX + HFD groups and the SHFD and OVX + HFD groups were fed a HFD for 28 weeks. Serum estrogen, testosterone, lipid, adiponectin, leptin, tartrate-resistant acid phosphatase (TRAP) and N -mid fragment of osteocalcin (N-MID-OT) levels were measured. Structure, apoptosis and specific transcription factors in bone were evaluated using pathologic, densitometric and immunohistochemical analysis. Body weight, serum leptin, TRAP and testosterone levels were increased, while serum N -MID-OT, estrogen and adiponectin levels were decreased in the SHFD, OVX and OVX + HFD groups. Expression of BCL2-associated X protein, caspase-3, matrix metalloproteinase-9 and calcitonin was increased, while bone mineral density (BMD) and content (BMC) in femurs and lumbar spine, and expression of B cell lymphoma 2, type 1 collagen and osteocalcin were decreased in the bones of the SHFD, OVX and OVX + HFD groups. All indices were greatest in the OVX + HFD group and HFD produced a detrimental effect on bone in both normal and OVX rats, which may be due to increased apoptosis in bone and increased leptin and decreased adiponectin levels in serum. The effects of HFD and OVX may be synergistic.